Developing Entrance Ticket and Exit Card as Formative Assessment for Promoting Learner Autonomy of Struggling Students - Yogyantoro, Yogyantoro (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Struggling students risk leaving school without having the opportunity to develop their independence to become less reliant on others. This study aims to gain insights into how formative assessment as a teaching design can support self-regulated learning (SRL) among struggling students. Entrance Ticket and Exit Card are short prompts that can provide instructors with a quick student diagnostic. These exercises can be collected on 6”x4” cards or small pieces of paper. Formative assessment is most effective when administered often. Efficiency is ensured when the information identified is evaluated immediately and the results are applied directly in the next lesson. The study was conducted to determine the perceptions of students and experts regarding using entrance tickets and exit cards for promoting students' learning autonomy. This ADDIE research and development study was conducted to develop entrance tickets and exit cards. After the product was created, a quasi-experimental design was used to determine the product's effectiveness toward learner autonomy. The result revealed feasible evaluations from the students and the experts regarding the product. Statistical processes using the independent t-test analysis in comparing the achievement between the control and experimental groups showed significant differences between the groups based on the "Independent Samples Test" output table in the "Equal variances not assumed" row, it is generated that the value of Sig. (2-tailed) of 0.00 <0.05. The experimental group showed above average with overall total mean score of 3.846 level of learner autonomy. The implications of this study extend to teachers, students, and future researchers, providing valuable insights and directions for the advancement and improvement of language education.